Kebutuhan Khusus pada Permasalahan Psikologi Perempuan pada Kehamilan tidak Diinginkan dengan Hipnoterapi - Ririn Ariyanti; Ika Yulianti (Jurnal Kesehatan Mahardika, 2022)
Unwanted pregnancy status can have an impact on the psychological aspects of pregnancy. Hypnotherapy is one of the special needs that need to be given to overcome psychological problems in unwanted pregnancies. This research has not been done much in Indonesia. The purpose of the study was to find out the effect of hypnotherapy on women's psychological problems in unwanted pregnancies. Methods of using systematic review. Research from as many as 454 articles later analyzed PRISMA into 9 articles came from databases such as Pubmed, Science Direct, google scholar. The results showed that the pooled odds ratio obtained by 0.07 (95% CI 0.04 – 0.15) so that it can be concluded that hypnotherapy can reduce the risk of 0.07 mothers experiencing psychological problems and unwanted pregnancies are greater. There is a significant relationship between hypnotherapy and the incidence of psychological problems in pregnant women that are not desirable evidenced by p < 0.05 which is p = 0.00001.